Epidemiologic and etiologic characteristics of hand, foot, and mouth disease in Chongqing, China between 2010 and 2013. Issue 3 (9th November 2015) - Lai, Fang‐Fang; Yan, Qiang; Ge, Sheng‐Xiang; Tang, Xiang; Chen, Ru‐Juan; Xu, Hong‐Mei
Abstract : Hand, foot, and mouth disease (HFMD) has become very common in children, with widespread occurrence across China. The aim of this study was to investigate the epidemiologic and etiologic characteristics of HFMD, including etiologic variations in Chongqing, China. An epidemiologic investigation was based on 3, 472 patients who presented with HFMD manifestations and were admitted at the Children's Hospital of Chongqing Medical University between 2010 and 2013. Fecal specimens from 830 patients were analyzed by nested RT‐PCR to identify the enterovirus pathogens, and the molecular characterization of HFMD was illustrated by phylogenetic tree analysis. The results of this study indicate that the peak of the HFMD epidemic in Chongqing between 2010 and 2013 occurred between April and July each year. The median age of onset was 2.24 years old, and children under the age of five accounted for 96.4% of all the HFMD cases; the male‐to‐female ratio was 1.89:1. Enterovirus 71 accounted for a major proportion of the isolated strains every year, including the majority (74%) of severe cases. However, the proportion of Coxsackie A (CV‐A) 6 infections increased from 2.11% in 2010 to 16.36% in 2013, while the proportion of CV‐A16 infections decreased from 31.23% in 2010 to 4.67% in 2013. Molecular epidemiologic study showed that all enterovirus 71 strains belonged to subgenotype C4a, whereas all CV‐A16 strains belonged to genotype B1, including subgenotype B1a and subgenotype B1b. J. Med. Virol. 88:408–416, 2016 . © 2015 Wiley Periodicals, Inc.